Embodying Compassion: Disability Sport and the Mercy of God - Brock, Brian (Journal of disability & religion, 2017)
The author offers a robustly theological account of compassion, highlighting its bodily nature. Divine mercy is presented as being conveyed through human bodies to remake and enliven both the human agent and recipient. Culminating in a story of a physically and mentally impaired runner, this account of mercy and compassion fleshes out God's mercy, which can be understood as flowing through human bodies in the context of sporting activities. A challenge is thus levied at modern secularized accounts of compassion and mercy, as well as many of the dominant values in contemporary sport - flawless athletic beauty, agonistic competition, and financial success - which have rendered simple acts of intercompetitive compassion and mercy nearly unintelligible.